Quantitative differential scanning calorimetric analysis for determining total polar compounds in heated oils - Tan, C. P.; Che Man, Y. B. (Wiley, 1999)
A new differential scanning calorimetry (DSC) method was developed for the determination of total polar compounds (TPC) in heated oils. Three different types of edible oils, refined, bleached, and deodorized corn oil (CO), palm olein (RBDPO), and soybean oil (SO), were used in this study, Each type of edible oil was heated at 180°C in a deep fryer to obtain a range of TPC concentrations. In this study, the cooling thermograms of oil samples at a scanning rate of 1°C/min from −30 to −85°C showed a well-defined single crystallization peak. The study found that six DSC parameters, namely, peak temperature (PT), enthalpy (EN), onset (ON) and offset (OF) temperatures, peak height (HT), and the range of temperatures (RT) (the difference between onset and offset temperature) of this single crystallization peak could predict well the TPC of heated oils by using stepwise multiple linear regression analysis. These six parameters were used as independent variables while values from standard method were used as dependent variables. The coefficient of determination (R2) of calibration models for CO, RBDPO, and SO were 0.9996, 0.9709, and 0.9980, respectively. Calibration models were validated with an independent set of samples. The R2 of validation models were 0.9995, 0.9559, and 0.9961, respectively. Based on the results obtained, DSC appears to be useful instrumental method in determining the TPC of edible oils, and it may have the potential to replace the time- and chemical-consuming standard method.